Frequency distribution and risk factors of hepatitis B virus and hepatitis C virus infections among thalassemia patients: a regional study. Issue 2 (February 2019) - Shah, Tariq; Hussain, Wajid; Ali, Niyaz; Sardar, Sadia; Ishaq, Muhammad; Ur Rahman, Mujaddad; Ding, Luming; Qayyum, Sadia; Khan, Ibrar
Abstract : Background: Thalassemia is a group of inherited hematological disorders caused by mutation in globin's genes. Regular blood transfusion lengthens the life of thalassemia patients but it carries a definite risk of the infections of blood-borne diseases. Aim/Objective: The current study was carried out for the frequency distributions and risk factors of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections among thalassemia patients in Hazara regions, Pakistan. Methods: A total of 324 enrolled thalassemia major patients were diagnosed in five different centers of Hazara regions. The study participants were screened for HBV and HCV using the immunochromatographic techniques test and real-time PCR for immunochromatographic technique-positive specimens. Results: Out of the 324 major thalassemia patients, 24 (7.41%) were diagnosed with HBV and HCV infections. In total, 206 were male patients and the rate of HBV and HCV infections was 0.97% (two patients) and 3.88% (eight patients), respectively. Similarly, 118 were female patients and the rate of HBV-positive patients was 3.39% (four patients) and HCV was 8.47% (10 patients). The results also showed that 50% of HBV and HCV infections were found in the age group of 26–30 years, while 1.81% was found in the age group of 11–15 years. The positive HBV and HCV samples were also verified with the band size of 242 and 227 bp, respectively. Conclusion: Thus, to reduce the incidence of HBV and HCV in thalassemia patients, we must call for critical look on the transfusion practices as well as adoption of stricter donor selection.